Comportamento de parâmetros fisiológicos de homens e mulheres em condições de estresse laboral submetidos à técnica Watsu - Tavares, Larissa Bastos (2004)
The physiological variations of parameters in situations of laboral stress can function like indicator in the sprouting of disorder. Those conditions have led researchers to investigate alternatives that can favor the quality of life in persons under stress laboral. The present research had as objectives investigate the physiological behavior of parameters (blood pressure, heart hat and respiratory hat) of men and women in condition of stress laboral submitted to the technique Watsu. It was used a experimental methodology with a group formed by men and women in reproductive age, that work as salesclerk in a supermarket net in Natal/RN. The seven individuals selected were submitted to the three phases of the study (dependent groups), that consisted of the phase 1 of obtaining from the measure basal (control 1), in the phase 2 of immersion in the water (control 2), and phase 3 from the application the technique Watsu (experimental phase). It was verified that during the phase basal (condition 1) the physiological parameters (BPS, BPD, HH and RH) of both sexes evaluated showed the medium values of the women (average±detour-standard: BSP = 104.1±7.92; BPD = 70.83 ±7.92; HH = 77.58 ±3.87; RH = 19.83 ±2.58) similar those presented by the men (BPS = 118.75 ±7.55; BPD = 75.00 ±9.91; HH = 71.75 ±14.95; RH = 16.62 ±3.99). The evaluation of those parameters before and after immersion of the volunteers in the water (condition 2) showed a significant reduction (W = 3.0: p≤0.05) barely for the values of BPS presented by the sex females after immersion. In the men group, all of the physiological parameters analyzed did not vary significantly. Regarding the profile of those variables before and after application of the watsu (condition 3), was verified a significant increase (W= 0,0: p≤0.05) for the BPS one and SABP in the women. The Men did not show significant variation for all of the physiological parameters. Faced with the results presented, we are able to conclude that the systolic and diastolic blood pressures were the physiological parameters that are on influence from the Technique Watsu, only for the kind females